AusGeochem: An Open Platform for Geochemical Data Preservation, Dissemination and Synthesis. Issue 2 (1st March 2022) - Boone, Samuel C.; Dalton, Hayden; Prent, Alexander; Kohlmann, Fabian; Theile, Moritz; Gréau, Yoann; Florin, Guillaume; Noble, Wayne; Hodgekiss, Sally‐Ann; Ware, Bryant; Phillips, David; Kohn, Barry; et al.
Abstract : To promote a more efficient and transparent geochemistry data ecosystem, a consortium of Australian university research laboratories called the AuScope Geochemistry Network assembled to build a collaborative platform for the express purpose of preserving, disseminating and collating geochronology and isotopic data. In partnership with geoscience‐data‐solutions company Lithodat Pty Ltd, the open, cloud‐based AusGeochem platform (https://ausgeochem.auscope.org.au ) was developed to simultaneously serve as a geosample registry, a geochemical data repository and a data analysis tool. Informed by method‐specific groups of geochemistry experts and established international data reporting practices, community‐agreed database schemas were developed for rock and mineral geosample metadata and secondary ion mass spectrometry U‐Pb analysis, with additional models for laser ablation‐inductively coupled‐mass spectrometry U‐Pb and Lu‐Hf, Ar‐Ar, fission‐track and (U‐Th‐Sm)/He under development. Collectively, the AusGeochem platform provides the geochemistry community with a new, dynamic resource to help facilitate FAIR (Findable, Accessible, Interoperable, Reusable) data management, streamline data dissemination and advanced quantitative investigations of Earth system processes. By systematically archiving detailed geochemical (meta‐)data in structured schemas, intractably large datasets comprising thousands of analyses produced by numerous laboratories can be readily interrogated in novel and powerful ways. These include rapid derivation of inter‐data relationships, facilitating on‐the‐fly data compilation, analysis and visualisation. Abstract : Key Points AusGeochem is an open, cloud‐hosted geospatial platform for global geochemistry data. It simultaneously serves as a geosample registry, geochemistry data repository and data interrogation tool, which can be accessed by external systems via its application programming interface. Its relational database architecture enables analytics to be performed across geochemistry data types.